(untitled) (Italian Review of Legal History, 2015)
Gian Domenico Romagnosi’s contribution to the restructuring of legal studies in Italy – a reform unfurled through plans and bills, namely the Piano di istruzione legale (Legal Education Plan) and Progetto di Regolamento degli Studi Legali (Project for the Regulation of Legal Studies) and, from a legislative point of view, through the formation of the Regolamento per gli studi Pratici Legali (Regulations for Practical Legal Studies), as well as the creation of three Postgraduate Schools – culminating in the drafting of an unpublished textbook entitled Introduzione enciclopedica allo studio del diritto. his work still strove to collect and explain knowledge: as such, it was a sort of manifestation of the goals he had alluded to ten years earlier in Studio preparatorio alla Facoltà Politico Legale. His Introduzione was meant to be just that: ‘introductory tool’ that could embrace the whole of legal knowledge, so that the elderly Professor could take stock of his educational ambitions and disseminate the epistemological views that he identified with in the new institutional climate. Romagnosi came to this subject matter late in life, having left behind the various forms of individualistic radicalism that had typified the revolutionary era and his encyclopedia seems to be an appropriate way to summarize his life’s work.